Genomic and Functional Characterization of Poultry Escherichia coli From India Revealed Diverse Extended-Spectrum β-Lactamase-Producing Lineages With Shared Virulence Profiles - Hussain, Arif; Shaik, Sabiha; Ranjan, Amit; Suresh, Arya; Sarker, Nishat; Semmler, Torsten; Wieler, Lothar H.; Alam, Munirul; Watanabe, Haruo; Chakravortty, Dipshikha; Ahmed, Niyaz (Frontiers in Microbiology, 2019)
Extended-spectrum β-lactamases (ESBLs) form the most important resistance determinants prevalent worldwide. Data on ESBL-producing Escherichia coli from poultry and livestock are scarce in India. We present data on the functional and genomic characterization of ESBL-producing E. coli obtained from poultry in India. The whole genome sequences of 28 ESBL-producing E. coli were analyzed comprising of 12 broiler chicken E. coli isolates, 11 free-range chicken E. coli isolates and five human Extraintestinal pathogenic E. coli. All of the 28 ESBL-producing E. coli isolates were tested for antibiotic susceptibilities, in vitro conjugation, and virulence-associated phenotypic characteristics. A total of 13 sequence types were identified from the poultry E. coli which included globally successful sequence types such as ST117 (9%), ST131 (4.3%), and ST10 (4.3%). The most common ESBL gene detected in poultry E. coli genomes was blaCTX-M-15 (17%). Also, FIB (73%) and FII (73%) were the most common plasmid replicons identified. Conjugation experiment demonstrated 54% (7/13), 30% (3/10) and 40% (2/5) of broiler, free-range and human ExPEC E. coli to be able to transfer their ESBL genes, respectively. The in vitro virulence-associated phenotypic tests revealed the broiler, free-range, and human ExPEC isolates to be comparable in biofilm formation, resistance to serum bactericidal activity, adherence and invasion capabilities. Our overall results showed prevalence of virulence phenotypes among the diverse ESBL-producing E. coli from poultry; while certain E. coli clones from broiler-poultry may indeed have the potential to cause infection in humans.